THE WORLD IS RAPIDLY SHIFTING FROM PAX-AMERICANA TO PAX-CHINA DURING THE COVID-19 ERA: A CRITICAL ANALYSIS - Dr Sarfraz Batool, Mahwish Abdullah, Muhammad Madni Asghar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The idea of Pax-China is not older than a few years ago. It caught the attention of scholars, global and socio-economic think tanks after china’s giant project "OBOR Initiative". But China had been ready to become a global player almost four decades before when it decided to rejoin the global economy through adopting a peaceful development strategy. For a long time, global think tanks had of their opinion that, though China is growing as a global power it could not supersede American hegemony in any way. America, in the Trump regime, sensed the real threat from China and waged a trade war against China. However, the out broke of COVID-19 and the way China and America dealt with the challenges of that pandemic abruptly shook the American hegemony. This paper, through a historical approach, will analyze the rise and fall of Pax-Americana and it will also precipitate that how the period of the pandemic has accelerated the process of Pax-China?